Treatment outcomes of elderly salivary gland cancer patients undergoing radiotherapy – Results from a large multicenter analysis. (March 2021) - Akbaba, Sati; Rühle, Alexander; Rothhaar, Sofie; Zamboglou, Constantinos; Gkika, Eleni; Foerster, Robert; Oebel, Laura; Klodt, Tristan; Schmidberger, Heinz; Grosu, Anca-Ligia; Debus, Jürgen; Bostel, Tilman; et al.
Highlights: Dose escalation ≥ 70 Gy improves local control of elderly salivary gland cancer patients. Low-to-moderate acute and chronic toxicities with no grade 4/5 toxicities. Performance status, T and N stage are prognosticators for local control and survival. Concomitant chemotherapy does not improve local control or survival. Resection with postoperative radiotherapy is superior to definitive radiotherapy. Abstract: Background and purpose: To evaluate oncological outcomes and treatment-related toxicities of elderly salivary gland cancer patients undergoing (chemo)radiotherapy. Material and methods: Local/locoregional control (LRC), progression-free survival (PFS) and overall survival (OS) of elderly patients ≥ 65 years with primary salivary gland cancers undergoing (chemo)radiotherapy between 2005 and 2020 at three tertiary cancer centers were calculated. The impact of clinicopathological and treatment parameters on outcomes were analyzed, and acute and chronic toxicities were quantified. Results: 288 elderly salivary gland cancer patients were included in this multicenter analysis, and their median LRC, PFS and OS amounted to 113, 39 and 75 months, respectively. Age, performance status, comorbidities, definitive vs. adjuvant (chemo)radiotherapy as well as locally/locoregionally advanced cancers and distant metastases correlated with reduced outcomes in elderly salivary gland patients. Patients receiving dose-escalated radiotherapy (total doses > 70 GyEQD2 ) with carbon ion boost radiation resulted in improved LRC, but no improvements in PFS or OS. Concomitant chemoradiotherapy did not improve treatment outcomes in elderly salivary gland carcinoma patients. Radiotherapy of elderly salivary gland cancer patients resulted in moderate higher-grade toxicities despite dose escalation with 70 (24.3%) and 48 patients (16.7%) experiencing acute and chronic grade 3 toxicities, respectively. No grade 4/5 toxicities were observed in this patient cohort. Conclusion: Data from the largest multicenter analysis of elderly salivary gland cancer patients undergoing (chemo)radiotherapy demonstrate favorable LRC and tolerable toxicity rates. Decision-making for these vulnerable patients should be based on patient performance rather than chronological patient age.